An rfaH Mutant of Salmonella enterica Serovar Typhimurium is Attenuated in Swine and Reduces Intestinal Colonization, Fecal Shedding, and Disease Severity Due to Virulent Salmonella Typhimurium - Bearson, Bradley L.; Bearson, Shawn M. D.; Kich, Jalusa D.; Lee, In Soo (Frontiers in Veterinary Science, 2014)
Swine are often asymptomatic carriers of Salmonella spp., and interventions are needed to limit colonization of swine to enhance food safety and reduce environmental contamination. We evaluated the attenuation and potential vaccine use in pigs of a Salmonella enterica serovar Typhimurium mutant of rfaH, the gene encoding the RfaH antiterminator that prevents premature termination of long mRNA transcripts. Pigs inoculated with wild-type S. Typhimurium exhibited a significant elevation in average body temperature (fever) at 1 and 2 days post-inoculation; rfaH-inoculated pigs did not (n=5/group). During the 7 day trial, a significant reduction of Salmonella in the feces, tonsils, and cecum were observed in the rfaH-inoculated pigs compared to wild-type inoculated pigs. To determine whether vaccination with the rfaH mutant could provide protection against wild-type S. Typhimurium challenge, two groups of pigs (n=14/group) were intranasally-inoculated with either the rfaH mutant or a PBS placebo at 6- and 8-weeks of age and challenged with the parental, wild-type S. Typhimurium at 11-weeks of age. The average body temperature was significantly elevated in the mock-vaccinated pigs at 1 and 2 days post-challenge, but not in the rfaH-vaccinated pigs. Fecal shedding at 2 and 3 days post-challenge and colonization of intestinal tract tissues at 7 days post-challenge by wild-type S. Typhimurium was significantly reduced in the rfaH-vaccinated pigs compared to mock-vaccinated pigs. Serological analysis using the IDEXX HerdChek Swine Salmonella Test Kit indicated that vaccination with the rfaH mutant did not stimulate an immune response against LPS. These results indicate that vaccination of swine with the attenuated rfaH mutant confers protection against challenge with virulent S. Typhimurium but does not interfere with herd level monitoring for Salmonella spp., thereby allowing for differentiation of infected from vaccinated animals (DIVA).